1998
DOI: 10.1159/000015158
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 5-methylcytosine in metaphase chromosomes of diploid and triploid pacu fish, <i>Piaractus mesopotamicus</i> (Pisces, Characiformes)

Abstract: The distribution of 5-methylcytosine (5-MeC) was investigated in fish chromosomes by indirect immunofluorescence using a highly specific 5-MeC monoclonal antibody. Diploid and artificially produced triploid specimens of the pacu fish, Piaractus mesopotamicus, were analyzed. The strong immunofluorescent signals were coincident with the heterochromatic regions of both diploids and triploids in a pattern that matched the C-banding pattern. In the euchromatin, heterogeneous labeling was observed along the chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most Gbanding seems to be due to heterochromatin, which in turn may be associated with methylation (de Almeida-Toledo et al, 1998), so that sex determination is epigenetically controlled (Negrutiu et al, 2001). To test this, correlate dioecy/cosexuality with the proportion of differential chromosomal G-banding, especially where only one sex has heteromorphically banded putative proto-sex chromosomes.…”
Section: Methylation Can Canalize Dioecymentioning
confidence: 99%
See 1 more Smart Citation
“…Most Gbanding seems to be due to heterochromatin, which in turn may be associated with methylation (de Almeida-Toledo et al, 1998), so that sex determination is epigenetically controlled (Negrutiu et al, 2001). To test this, correlate dioecy/cosexuality with the proportion of differential chromosomal G-banding, especially where only one sex has heteromorphically banded putative proto-sex chromosomes.…”
Section: Methylation Can Canalize Dioecymentioning
confidence: 99%
“…To test this, correlate dioecy/cosexuality with the proportion of differential chromosomal G-banding, especially where only one sex has heteromorphically banded putative proto-sex chromosomes. Most Gbanding seems to be due to heterochromatin, which in turn may be associated with methylation (de Almeida-Toledo et al, 1998), so that sex determination is epigenetically controlled (Negrutiu et al, 2001). G-banding data (Solari, 1994) and robust phylogenies (Olmo, 1986;Baldauf et al, 2000;Cao et al, 2000a;Gissi et al, 2000) exist, including in lineages for which there is evidence that differential methylation may be the first step in differentiation of sex chromosomes.…”
Section: Methylation Can Canalize Dioecymentioning
confidence: 99%
“…To our knowledge, up to date a single cytogenetic analysis on the occurrence of 5-MeC-rich chromosome regions has been carried out in fishes [Almeida-Toledo et al, 1998]. In this study, diploid and artificially produced triploid individuals of the pacu fish, Piaractus mesopotamicus , were labeled with a monoclonal anti-5-MeC antibody which demonstrated that 2 constitutively heterochromatic regions are enriched with 5-MeC.…”
mentioning
confidence: 97%
“…Thus far, GC-rich heterochromatin have only been previously reported in the cyprinid Gobio gobio (Kirtiklis et al 2005), in several other fish species of the genus Chromaphyosemion (Völker et al 2005) and in the lamprey Lampetra zanandreai (Caputo et al 2011). As also happens in the fish Piaractus mesopotamicus (Almeida-Toledo et al 1998), the bright signals obtained after 5-methylcytosine immunolocation are located in the GC-rich heterochromatic regions, demonstrating that on meiotic chromosomes these regions are highly methylated and, therefore, transcriptionally repressed (Jaenisch and Bird 2003).…”
Section: Discussionmentioning
confidence: 96%